Access, Equity and Quality of Guidance and Counselling Education in the Face of Insecurity in Bayelsa State, Nigeria (Federal University Gusau Faculty of Education Journal, 2025)
The study was conducted to determine access, equity and quality of guidance and counselling education in the face of insecurity in Nigeria. This research was descriptive in form. This design was used to gather information from a sampled of students. The population of the study comprised 3622 students in 44 secondary schools in Southern Ijaw Local Government Area of Bayelsa State. The sample of the study include 300 students of SSI – SSIII classes. The students were selected from 30 secondary schools because of the ease of accessibility of the schools. A structured questionnaire containing 17 items and validated by experts, was use for data collection. The data collected was analysed with the use of simple percentage and mean. The result indicated that guidance and counselling education are not accessible, not equitable and of poor quality due the inadequacy of counselling personnel, inadequate funding, unavailability of needed facilities etc. The paper concluded that the inadequacy gap in guidance and counselling education remains the major reason insecurity persist in our society. The paper recommends the provision of necessary tools to improve guidance and counselling services in our schools.